Coffee has hepatoprotective benefits in Brazilian patients with chronic hepatitis C even in lower daily consumption than in American and European populations - Machado,Silmara Rodrigues (2014)
The potential role of coffee as a hepatoprotective substance for chronic liver diseases has been widely discussed. Our main aim was to evaluate the effect of coffee intake regarding clinical, biochemical tests and liver biopsy data in treatment naïve patients with chronic hepatitis C. One hundred and thirty-six patients with chronic hepatitis C, diagnosed through liver biopsy, or by means of clinical, ultrasound or endoscopic signs of cirrhosis, were assessed by determination of biochemical tests, metabolic and morphological alterations. Food frequency was scrutinized by using a structured questionnaire. Coffee intake represented more than 90% of the total daily caffeine, and the 75th percentile was 4-Brazilian coffee-cup/day (>255mL/day or >123mg caffeine/day). According to caffeine intake, patients were divided into two groups (< or >123mg caffeine/day). Patients with higher ingestion of caffeine had lower serum levels of aspartate aminotransferase (× upper limit of normal) (1.8±1.5 vs 2.3±1.5, p=0.04), lower frequencies of advanced (F3, F4) fibrosis (23.5% vs 54.5%, p<0.001) and of histological activity grade (A3, A4) observed in liver biopsies (13.8% vs 36.9%, p<0.001). By multivariate logistic regression, fibrosis was independently associated with caffeine intake (OR- 0.16; 95%CI - 0.03-0.80; p=0.026), γ-glutamil transferase serum levels and morphological activity. But only fibrosis was associated with histological activity. In conclusion caffeine consumption greater than 123mg/day was associated with reduced hepatic fibrosis. In addition, this study supports the assumption that coffee intake has hepatoprotective benefits for Brazilian patients with chronic hepatitis C, even in lower doses than that of American and European population intake.